2013
DOI: 10.1166/jbn.2013.1613
|View full text |Cite
|
Sign up to set email alerts
|

Self-Nanoemulsifying Lipid Carrier System for Enhancement of Oral Bioavailability of Etoposide by <I>P</I>-Glycoprotein Modulation: <I>In Vitro</I> Cell Line and <I>In Vivo</I> Pharmacokinetic Investigation

Abstract: The purpose of this work is intended to investigate the potential of self-nanoemulsifying (SNE) drug delivery system for enhanced oral bioavailability of etoposide by P-glycoprotein (P-gp) modulation. The components of SNE formulation were optimized by their solubilization and emulsification efficiency. The ternary phase diagrams provided nanoemulsion existence ranges and the corresponding formulations were developed and evaluated via thermodynamic and dispersibility tests. The successful formulations were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…The poor solubility of such drugs does not only give low oral bioavailability, but also leads to interand intra-subject variability and lack of dose proportionality [23]. The selected excipients used in this study were reported as solubilizing agents for lipophilic candidates as well as permeation enhancers in emulsifying formulations [3][4][5]10]. The solubility of VP-16 was improved in the presence of selected pharmaceutical excipients and the maximum solubility was found to be in Solutol HS 15, Transcutol-P and Labrasol.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The poor solubility of such drugs does not only give low oral bioavailability, but also leads to interand intra-subject variability and lack of dose proportionality [23]. The selected excipients used in this study were reported as solubilizing agents for lipophilic candidates as well as permeation enhancers in emulsifying formulations [3][4][5]10]. The solubility of VP-16 was improved in the presence of selected pharmaceutical excipients and the maximum solubility was found to be in Solutol HS 15, Transcutol-P and Labrasol.…”
Section: Discussionmentioning
confidence: 87%
“…Sha et al [27] reported that oral bioavailability of gentamycin in rats was significantly enhanced when it was co-administered with Labrasol. The study of Akhtar et al [3] concluded that the improved oral bioavailability of VP-16 in the presence of surfactant could be explained by the significantly improved solubility of VP-16 by surfactant solubilization which could keep the drug as the soluble form during the gastrointestinal permeation process, and the inhibition of P-gp efflux of VP-16 by solution surfactants. Hence, feasibility of oral administration of VP-16 with P-gp inhibitory excipients was considerably improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(101) In our laboratory, SMEDD formulations for different anticancer drugs, based on Pgp modulation by using excipient having P-gp modulation activity, have been developed and showed many fold higher oral bioavailability. (108)(109) These studies revealed that the bioavailability of drugs can be improved by pgp modulation.…”
Section: P-glycoprotein Inhibition or Modulationmentioning
confidence: 99%
“…Recently, nanoformulations like nanoemulsion (Verma et al, 2015), self nanoemulsifying drug-delivery system (Akhtar et al, 2013;Negi et al, 2013), solid lipid nanoparticles (Yuan et al, 2013) polymeric micelles (Yao et al, 2011), Dendrimer (Ke et al, 2008), layersomes (Jain et al, 2012), polymeric NPs (Jain et al, 2011b;Fatma et al, 2014;Katiyar et al, 2015), protein NPs (Golla et al, 2013) etc. have gained considerable attention for successful oral delivery of anticancer agents.…”
Section: Introductionmentioning
confidence: 99%